2015
DOI: 10.1589/jpts.27.2327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-hour neuromuscular electrical stimulation treatment program on the recovery of upper extremity function in sub-acute stroke patients: a randomized controlled pilot trial

Abstract: [Purpose] This study investigated the effects of a 12-hour neuromuscular electrical stimulation program in the evening hours on upper extremity function in sub-acute stroke patients. [Subjects and Methods] Forty-five subjects were randomized to one of three groups: 12-hour neuromuscular electrical stimulation group (n=15), which received 12 hours of neuromuscular electrical stimulation and conventional rehabilitation for the affected upper extremity; neuromuscular electrical stimulation group (n=15), which rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In the study of Cui et al including 45 subjects, it was found that the FMA of 12-h neuromuscular electrical stimulation group was more significantly improved than that of the ordinary treatment group. This alternative therapy is easy to apply and can be used during rest or sleep in stroke patients [13]. There is now much The score after treatment of combined treatment group compared with that before treatment, P < 0.001; compared with LFPEST group, P < 0.001; compared with MIT group, P < 0.001.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the study of Cui et al including 45 subjects, it was found that the FMA of 12-h neuromuscular electrical stimulation group was more significantly improved than that of the ordinary treatment group. This alternative therapy is easy to apply and can be used during rest or sleep in stroke patients [13]. There is now much The score after treatment of combined treatment group compared with that before treatment, P < 0.001; compared with LFPEST group, P < 0.001; compared with MIT group, P < 0.001.…”
Section: Discussionmentioning
confidence: 96%
“…With the development of rehabilitation medicine, MIT has become an important strategy for exercise function rehabilitation, and is gradually applied to the recovery of upper limb function in stroke patients [10,11]. Low-frequency pulsed electrical stimulation therapy (LFPEST), also known as neuromuscular electrical stimulation therapy, mainly stimulates the relevant nerves and muscles by electric current to produce passive contraction and promote the recovery of damaged neuromuscular functions [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the RFE under the NMES group significantly improved distal motor paralysis compared to the CT group. Cui et al reported that 12 hours a day of NMES was effective in improving wrist and finger paralysis in the paralyzed upper limb with subacute stroke patients [ 23 ]. Moreover, Lin and Yan reported that 30 minutes/day of rehabilitation focusing on the movement induced by NMES for severe paralyzed patients improved upper limb function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This allowed normal arm movement with swing phase flexion and stance phase extension patterns to be produced with repetitive practice. The specific parameters of the FES were as follows: i) frequency=20–40 Hz; ii) pulse width=200–400 ms; iii) amplitude=biphasic waveform of 20–50 mA; and iv) an on/off ratio of 1:1 11 ) . The FES was discontinued after 3 weeks, at which point the patient was able to fully extend his elbow independently.…”
Section: Sebject and Methodsmentioning
confidence: 99%